PENERAPAN ACTIVE LEARNING DENGAN SILENT DEMONSTRATION UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA KELAS VIII D SMP NEGERI 14SURAKARTA - Nurhemy, Try Nesia; Santosa, Slamet; Probosari, Riezky Maya (P Biologi FKIP UNS Surakarta, 2011)
ABSTRACT ? The purpose ofthis study was to improvestudent science process skills on Biology teaching by implementation of Active Learning with Silent Demonstrationand increaselearning outcome by improvingstudent science process skills. This research usedclassroom action research. The experiment was conducted in two cycles, with each cycle consisting of the planning, acting, observation, and reflection. Subjects were students of class VIII-DSMP Negeri 14 Surakarta academic year 2010/2011. Source of data derived from teacher and student information, places and events on going learning activities, and documentation. Techniques and tools of data collection are questionnaire, observation, and interviews. Technical analysis of data is using qualitative descriptive. Data validationis use methods triangulation Result of the research showed that with action performing brazes to pass through Implementation of Active Learning with Silent Demonstration can improve science process skillsin biology learning in class VIII-DSMP Negeri 14 Surakarta academic year 2010/2011. It wasgone upon on questionnaire result, observation and interview. The average percentage each indicator of student activities based on observation for pre cycle is 36,62%, a cycle of 68,94% and 78,28% for cycle 2. The conclusions that application of Active Learning with Silent Demonstrationcan improve student science process skillsand learning outcome by improvingstudent science process skills. Keywords: Active Learning, Silent Demonstration, Science Process Skills